2021
DOI: 10.4314/mmj.v33i2.7
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported and clinically evident gingival bleeding and impact on oral health-related quality of life in young adolescents: a comparative study

Abstract: BackgroundVery little is known about how self-reported gingival bleeding affects the oral health-related quality of life in adolescents compared with clinically evident bleeding. This study aimed to compare the impact of self-reported gingival bleeding and clinically evident gingival bleeding on the oral health-related quality of life in young adolescents.MethodsThis was a cross-sectional study involving 976 students (aged 10–14 years) in randomly selected primary schools in Ibadan. Data were obtained by oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…Females are also reported to be more affected than males [9] although some studies did not nd any sex differences [10,11]. Some studies in SSA report no age difference in the prevalence of oral impacts [10,12] while others have found that older adolescents tend to report oral impacts more frequently than their younger counterparts [9]. Similar age distribution of C-OIDP has also been observed in studies from high-income countries [2].…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…Females are also reported to be more affected than males [9] although some studies did not nd any sex differences [10,11]. Some studies in SSA report no age difference in the prevalence of oral impacts [10,12] while others have found that older adolescents tend to report oral impacts more frequently than their younger counterparts [9]. Similar age distribution of C-OIDP has also been observed in studies from high-income countries [2].…”
Section: Introductionmentioning
confidence: 70%
“…Adolescents with dental caries report oral impacts about one to ve times more often than those without [7]. Gingivitis is also related to oral impacts as reported in some studies although to a lesser extent than dental caries [8,9]. Independent of clinical measures of oral diseases, C-OIDP has been associated with sociodemographic, behavioral, and psychological factors in various populations, showing that the poor, socially disadvantaged, and those living in rural areas are most negatively affected (2,7,10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La salud bucal es indispensable para conseguir el bienestar general; cuando existe dolor dentario o sangrado gingival en un niño se afecta su calidad de vida [1][2][3][4][5] . La caries es la enfermedad más prevalente en la cavidad oral, siendo su principal problema etiológico la alta frecuencia de ingesta de azúcares libres, en los niños se debe limitar su consumo mediante alimentos y bebidas que lo contengan 6,7 .…”
Section: Introductionunclassified